Requalificação do hipercentro de Belo Horizonte: possibilidades de inserção do uso residencial - Mateus Moreira Pontes (2006)
Since the 70s the central areas of Brazilian cities have been suffering a gradual reduction of its population and of its economical status due to the displacement of the dominant classes in search for new centralities. The degrading phenomenon caused by this reduction can be perceived by the expressive number of empty buildings in bad conditions of preservation as also by the expressive reduction of residents in such areas. Initiatives of rehabilitation of central areas of cities have become the focus of the Brazilian urban debate in the last few years, which has gained force with the promulgation of the Statute of the Cities and the foundation of the Ministry of the Cities. Affordable housing has been debated withincontemporary discussions as a strategical approach to increase population and consequently enable the requalification of such central areas. Within this context this dissertation discusses the actual state of Belo Horizontes hyper-centre, characterising its emptiness anddegradation, the role of the housing market and of the urban legislation in the requalification process, and also the possibilities for producing affordable housing in the central area of the Capital.